The Attractiveness of Education - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 1997)
The long-existent school problem of pupils’ reluctance to go to school and learn is valid today. This article tries to make some suggestions for the achievement of more attractive educational work and school.